Synthesis and Antimicrobial activity 2-chloro-6-methylquinoline Hydrazone derivatives - Rajiv Kumar; Suresh Kumar; Sushma Drabu; Sandhya Bawa (Wolters Kluwer Medknow Publications, 2009)
A series of 2-chloro-6-methylquinoline hydrazones (3a-o) were synthesized by the condensation of substituted acyl hydrazines, semicarbazide, thiosemicarbazide and INH with 2-chloro-3-formyl-6-methylquinoline in absolute alcohol. The structures of compounds were established using spectral data and elemental analysis. All the compounds were evaluated for their antibacterial activity against Escherichia coli (NCTC, 10418), Staphylococcus aureus (NCTC, 65710) and Pseudomonas aeruginosa (NCTC, 10662). Compounds were also tested for antifungal activity aganist Aspergillus niger (MTCC, 281), Aspergillus flavus (MTCC, 277), Monascus purpureus (MTCC, 369) and Penicillium citrinum (NCIM, 768) by cup-plate method.